The Importance of Identifying Early Childhood Learning Styles to Optimize Children's Achievement - Mar’atus Salamah; Dede Nursamsy; Siti Amelia; Wulandari Wulandari (International Journal Labs, 2026)
Early childhood education (PAUD) is an important stage in the cognitive, affective, and psychomotor development of children. Identification of children's learning styles from an early age allows educators to adjust learning methods according to the unique characteristics of the child, so that it can improve learning achievement and psychosocial development. This study examines the identification of learning styles of children aged 5-6 years in learning in PAUD, the influence of learning strategies that are in accordance with learning styles on the effectiveness and learning achievement, and the challenges faced by educators in their implementation. This study involved children aged 5-6 years in the surrounding environment for direct observation. The results showed that out of 9 children there was a dominant learning style, 4 children tended to have a visual learning style, 3 children had an auditory learning style, 2 children had a kinesthetic learning style and adjustment of learning methods could improve children's motivation, engagement, and learning outcomes. However, educators face obstacles in recognizing and implementing children's learning styles due to limited training and resources. To overcome this problem, teachers need to be given special training to understand and implement the right learning style for children. In addition, strengthening of facilities and infrastructure, as well as support from the surrounding environment is needed.